2018
DOI: 10.1186/s12544-018-0323-7
|View full text |Cite
|
Sign up to set email alerts
|

Options for reducing external costs from freight transport along the Brenner corridor

Abstract: The Brenner is the most heavily travelled transalpine corridor in terms of freight transport. The current modal split tends heavily towards road (71% road -29% rail), with significant repercussions in terms of environmental and social impacts. Indeed, Alpine areas generate external costs that are up to four times higher than flat areas. The promotion of railway, which is the least impacting transport mode, has thus a strategic value. For this reason, the European Union, the Alpine macro-region and the Tyrol-So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Nocera et al [55] presented options for reducing external costs from freight transport along the Brenner corridor. The current modal split in the studied region tended heavily towards road (71% road -29% rail), and the objective is to achieve (29% road -71% rail) by 2035.…”
Section: External Costsmentioning
confidence: 99%
“…Nocera et al [55] presented options for reducing external costs from freight transport along the Brenner corridor. The current modal split in the studied region tended heavily towards road (71% road -29% rail), and the objective is to achieve (29% road -71% rail) by 2035.…”
Section: External Costsmentioning
confidence: 99%
“…Indeed, a previous report showed that the line or mobile source contribute 21.2% of PM2.5 in Taiwan [45]. Therefore, transportation systems should be discussed, including electronic transport tools [51][52][53].…”
Section: Limitationsmentioning
confidence: 99%
“…At the same time, Kaack et al [5] find that many countries lack such policies. Nocera et al [26] use a different, but comparable taxonomy, dividing instruments that can (in)directly encourage modal shift into push measures (making road transport less attractive) and pull measures (making rail and waterborne transport more attractive). For freight transport, push measures may include taxation, charges and tolls, and regulatory measures (e.g., orders and bans), while pull measures may include positive financial incentives for sea and rail transport or measures that improve reliability or infrastructure or reduce shipping costs.…”
Section: Instruments and Measures For Inducing Modal Shiftmentioning
confidence: 99%
“…The first four scenarios consider single policy measures, while the latter five scenarios consider combinations of the single measures and/or border-crossing implementation in the Nordic countries. Together, the scenarios cover both infrastructure/efficiency improvements and financial incentives (in line with [5]) and can be characterized as both push and pull measures [26]. Vierth et al [32] carried out a related analysis as in the current paper for the case of Sweden, using the Swedish national freight model to calculate modal shifts, environmental effects, and changes in logistics costs from several proposed policy measures.…”
Section: Scenariosmentioning
confidence: 99%